2003
DOI: 10.1128/jb.185.2.534-543.2003
|View full text |Cite
|
Sign up to set email alerts
|

FlhD/FlhC Is a Regulator of Anaerobic Respiration and the Entner-Doudoroff Pathway through Induction of the Methyl-Accepting Chemotaxis Protein Aer

Abstract: The regulation by two transcriptional activators of flagellar expression (FlhD and FlhC) and the chemotaxis methyl-accepting protein Aer was studied with glass slide DNA microarrays. An flhD::Kan insertion and an aer deletion were independently introduced into two Escherichia coli K-12 strains, and the effects upon gene regulation were investigated. Altogether, the flhD::Kan insertion altered the expression of 29 operons of known function. Among them was Aer, which in turn regulated a subset of these operons, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
63
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(65 citation statements)
references
References 63 publications
(49 reference statements)
1
63
0
Order By: Relevance
“…The Aer-only UU1250 strains partially restored swarming in semisolid agar. In addition, they were resistant to oxygen depletion in liquid media, consistent with the induction by Aer of anaerobic respiration pathway components at low oxygen tension (39). In brief, the strains remained vigorously motile in the bridged coverslip chambers for tens of minutes after oxygen depletion as monitored by resazurin (51), whereas UU1250 strains expressing Tar or Tsr became immediately immotile.…”
Section: Vol 188 2006 Blue-light Motility Responses In E Coli 3963mentioning
confidence: 84%
“…The Aer-only UU1250 strains partially restored swarming in semisolid agar. In addition, they were resistant to oxygen depletion in liquid media, consistent with the induction by Aer of anaerobic respiration pathway components at low oxygen tension (39). In brief, the strains remained vigorously motile in the bridged coverslip chambers for tens of minutes after oxygen depletion as monitored by resazurin (51), whereas UU1250 strains expressing Tar or Tsr became immediately immotile.…”
Section: Vol 188 2006 Blue-light Motility Responses In E Coli 3963mentioning
confidence: 84%
“…The GacS/GacA-Csr system is not likely to be affected by the activities of these commensals: first, the phenotype of the gacA mutant (Krediet et al, in review) is distinct from what is observed when the wild type is exposed to the commensals tested here, and, second, the commensals did not affect the expression of the gacA::lacZ reporter (Krediet, unpublished data). It is also unlikely that FlhDC is affected by the commensals: even though FlhDC in Enterobacteriacea is known to contribute to the regulation of both motility and metabolism (Pruss et al, 2003), the fact that none of the commensals inhibited swimming motility suggests that FlhDC is also an unlikely target of these activities. Therefore, these observations suggest that either the compounds target another regulatory cascade, or that different compounds disrupt swarming and the induction of enzymatic activities separately.…”
Section: Discussionmentioning
confidence: 99%
“…We do not yet know whether the same compound is involved in the inhibition of both swarming and catabolism of mucus components. However, if this were the case, it is possible to hypothesize that a higher-level regulatory system (GacS/GacA-Csr or FlhDC) (Romeo, 1998;Pruss et al, 2003;Park and Forst, 2006;Timmermans and Van Melderen, 2010) may be the target. The GacS/GacA-Csr system is not likely to be affected by the activities of these commensals: first, the phenotype of the gacA mutant (Krediet et al, in review) is distinct from what is observed when the wild type is exposed to the commensals tested here, and, second, the commensals did not affect the expression of the gacA::lacZ reporter (Krediet, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…The activity and stability of FlhDC are regulated by FliZ, FliT, and FliD, the downstream gene products in the flagellar regulon, by YdiV, an EAL-like protein acting as an anti-FlhD 4 C 2 factor, by ClpXP, an ATP-dependent protease, and by DnaK, a protein chaperone (1,45,46,58,59,62,67). Microarray studies suggest that FlhDC also functions as a global regulator involved in carbon metabolism and anaerobic respiration (38,39).…”
mentioning
confidence: 99%